The Death of Technology and the Emotional Vacuum in Don Delillo’s The Silence (2020) - Hachemi, Ibrahim; Nouioua, Amira Wafa (University ofAmmar Theledji -Laghouat, 2022)
Originally, technology had been considered as a sign of progression and human evolution, yet many invalidated its negative aspects forgetting it can be a double-edged sword. That is to say, despite changing the human life for the better in many ways, technology is destructive if not used wisely. Thus, this dissertation explores the death of technology and the emotional vacuum in Don Delillo’s dystopian novel The Silence (2020) in addition to other issues such as consumerism and the disconnection from oneself and others. Using the theory of postmodern nihilism, this paper analyzes how the novel portrays dread, paranoia and melancholia after the sudden shutdown. The process of this study includes the approach of literary criticism as well as the descriptive analytical method. The results show that over-reliance on technology caused mental disorders especially identity crisis and detachment from reality after the technological failure.